Modeling of Rail-Based Public Transportation Services for the Conversion of Private Vehicle Users to Public Transportation - Saputro, Soemino Eko; Abdurachman, Edi; Ricardianto, Prasadja; Nugroho, Sinung Tri; Wibowo, Heriyanto; Nugroho, Agus (Jurnal Manajemen Pelayanan Publik, 2024)
The issues contributing to the unpopularity of public transportation include a limited railway network, inadequate service quality, and incomplete integration. Additionally, the willingness to utilize public transportation is frequently affected by factors influencing passenger satisfaction and trust in the system. This study aimed to assess the efficacy of the public transportation service model, and the policies enacted; hence, multiple variables were utilized in the analysis. Subjective quality; belief; passenger satisfaction; value perception; commuter preference; commuter loyalty; intention to repurchase. Commuter preference serves as an intermediary element influencing the relationship between Belief and Commuter loyalty, hence enhancing loyalty. This study employs Importance and Performance Analysis and Structural Equation Modeling utilizing the SMART PLS program, along with Focus Group Discussions to investigate the topic, based on a sample of 400 respondents. The analysis indicates that subjective quality, satisfaction, trust, preferences, and loyalty positively influence loyalty and significantly affect the intention repurchase. Nonetheless, value perception does not substantially affect commuter loyalty. Operators must concentrate on ensuring seamless train travel, elevated reliability, effective integration, and a cohesive ticketing system to enhance service performance.